Optimal FSH usage in revascularization of allotransplanted ovarian tissue in mice. Issue 1 (December 2017) - Ma, Wen-Zhi; Zheng, Xiao-Min; Hei, Chang-Chun; Zhao, Cheng-Jun; Xie, Sha-Sha; Chang, Qing; Cai, Yu-Fang; Jia, Hua; Pei, Xiu-Ying; Wang, Yan-Rong
Abstract Backgroud Ovarian transplantation is a useful method for preserving the fertility of young women with cancer who undergo radiotherapy and chemotherapy. Follicle-stimulating hormone (FSH) is use to protect transplanted ovarian tissues from ischemia injury through promoting revascularization after transplantation, but the side effect of high level FSH is ovarian overstimulation leading to substantial follicular loss. In this study, we investigated the optimal usage of FSH on revascularization in the in vitro cultured ovarian tissues before and after transplantation. Results FSH mainly exhibited an additive response in the gene and protein expression of vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF) and follicle stimulating hormone receptor (FSHR) with its raised concentrations (0.15 IU/ml, 0.30 IU/ml and 0.60 IU/ml) and prolonged treatment (3 h, 6 h, 12 h, 24 h). The concentrations with 0.60 IU/ml FSH could obviously promoted the expression of VEGF, bFGF and FSHR, but under this concentration FSH could also overstimulated the ovarian tissue leading to follicular loss. With the increase of culture time, the gene and protein expression of VEGF and bFGF both were up-regulated in all of the FSH added groups, but FSHR expression decreased when culture time exceeded 12 h. So we chose 0.30 IU/ml FSH added concentration and 6 h culture time as the FSH usage condition in functional revascularization verification experiment, and found that under this condition FSH promoted 2.5 times increase of vascular density in treated group than in control group after ovarian tissues transplantation. Conclusion Ovarian intervention with 0.30 IU/ml FSH for 6 h is an optimal FSH usage condition which could accelerate the revascularization in the allotransplanted ovarian tissue and can not produce ovarian overstimulation.